2001
DOI: 10.4049/jimmunol.167.11.6631
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of 5-Lipoxygenase Accelerates Renal Allograft Rejection in Mice

Abstract: Acute renal allograft rejection is associated with alterations in renal arachidonic acid metabolism, including enhanced synthesis of leukotrienes (LTs). LTs, the products of the 5-lipoxygenase (5-LO) pathway, are potent lipid mediators with a broad range of biologic activities. Previous studies, using pharmacological agents to inhibit LT synthesis or activity, have implicated these eicosanoids in transplant rejection. To further investigate the role of LTs in acute graft rejection, we transplanted kidneys from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Previous reports have suggested a role of metabolites of the 5-lipoxygenase (5-LO) pathway and in particular the leukotrienes, in renal hemodynamics (Imig, 2000). Studies using 5-LO-deficient mice have also suggested a role for 5-LO metabolites in allograft rejection (Goulet et al, 2001); however, the precise role of 5-oxo-ETE and its receptor is not clear.…”
Section: Discussionmentioning
confidence: 97%
“…Previous reports have suggested a role of metabolites of the 5-lipoxygenase (5-LO) pathway and in particular the leukotrienes, in renal hemodynamics (Imig, 2000). Studies using 5-LO-deficient mice have also suggested a role for 5-LO metabolites in allograft rejection (Goulet et al, 2001); however, the precise role of 5-oxo-ETE and its receptor is not clear.…”
Section: Discussionmentioning
confidence: 97%
“…However, the contribution of 5-LOX metabolites to the regulation of the inflammatory response in more chronic settings of inflammation cannot be discounted. Indeed, there is evidence that the rejection of renal allografts is accelerated in 5-LOX Ϫ/Ϫ mice (Goulet et al, 2001).…”
Section: -Lipoxygenase In Renal I/r Injury 223mentioning
confidence: 99%
“…This is supported by the findings of Pinschewer et al, who demonstrated that FTY720 did not affect induction and expansion of cytotoxic T cells but caused a shift in distribution of lymphocytes from the spleen to the peripheral LNs (1). Conversely, failure of the contribution of the cysLT pathway to LN migration may be responsible for accelerated renal allograft rejection observed in 5-LO -/-mice (44). It is also possible that FTY720-driven homing to the LNs contributes to other aspects of immunosuppression.…”
mentioning
confidence: 99%